Financial & Managerial Accounting The Basis for Business Decisions - Williams, Jan R.; Bettner, Mark S.; Smith, Kevin R. (McGraw Hill, 2024)
Financial and Managerial Accounting: The Basis for Business Decisions continues to offer a solid foundation for students?who are learning basic accounting concepts. Known for giving equal weight to financial and managerial topics, the authors?emphasize the need for a strong foundation in both aspects of accounting. The authors made data driven revisions focusing?on where students were struggling and updated content accordingly. Updates have also been made to the high-quality end?of chapter problems and new Guided Example hint videos in Connect.